Investigation of the Structure and Dynamics of the Capsid–Spacer Peptide 1–Nucleocapsid Fragment of the HIV‐1 Gag Polyprotein by Solution NMR Spectroscopy1. (11th December 2013) - Deshmukh, Lalit; Ghirlando, Rodolfo; Clore, G. Marius
Abstract Structural studies of HIV‐1 Gag, the primary structural polyprotein involved in retroviral assembly, have been challenging, owing to its flexibility and conformational heterogeneity. Using residual dipolar couplings, we show that the four structural units of the capsid (CA)–spacer peptide 1 (SP1)–nucleocapsid (NC) fragment of HIV‐1 Gag (namely, the N‐ and C‐terminal domains of capsid, and the N‐ and C‐terminal Zn knuckles of nucleocapsid) have the same structures as their individually isolated counterparts, and tumble semi‐independently of one another in the absence of nucleic acids. Nucleic acids bind exclusively to the nucleocapsid domain and fix the orientation of the two Zn knuckles relative to one another so that the nucleocapsid domain/nucleic acid complex behaves as a single structural unit. The low 15N–{1H} heteronuclear NOE values (≤0.4), the close to zero values for the residual dipolar couplings of the backbone amides, and minimal deviations from random‐coil chemical shifts for the C‐terminal tail of capsid and SP1, both in the absence and presence of nucleic acids, indicate that these regions are intrinsically disordered in the context of CA–SP1–NC.